Histological and Ultrastructural Studies on Spleen of Kadaknath Fowl - Dharve, Anar Singh (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on spleen of twenty five Kadaknath birds from day old to thirty weeks onwards of age. Semi thin sections of spleen stained with toluidine blue and examined under light microscope for histological while ultrathin sections were stained with uranyl acetate and lead citrate for ultrastructural observations under transmission electron microscope. The external surface of the capsule was lined by a single layer of mesothelial cells. Some melanin pigments were found in the capsule and parenchyma of spleen. Underneath the capsule, the splenic parenchyma was divided into white pulp and red pulp without clear cut demarcation. With the advancement of age the amount of white pulp was increased. In red pulp more erythrocytes were present along with few reticulo-epithelial cells, plasma cells and thrombocytes. While in white pulp lymphocytes, reticulo-epithelial cells, granulocytes, agranulocytes and plasma cells were present. In group I and II more lymphoblast and small lymphocytes were present whereas in older age group i.e. group V more large lymphocytes and plasma cells were present.